Preliminary study of the species composition and the abundance of butterflies (Rhopalocera : Lepidoptera) in the Phu Quoc national park - Phuong, Bui Xuan (Academia Journal of Biology, 2014)
The study was carried out during the period of November and December, 2003 in  the Phuquoc national park (Phuquoc island, Kiengiang province, Southern of Vietnam). There were 120 butterfly species belonging to 78 genera, 9 families of Lepidoptera: Rhopalocera, inhabiting in this national park. There were 3 rare butterfly species found in there, such as: Zeuxidia masoni Moore, 1878 (Amathusiidae), Troides aeacus C&R Felder, 1860 (Papilionidae) and Chilasa paradosa Zinken, 1831 (Papilionidae).